(untitled) (International Journal of Engineering and Computer Science, 2013)
Voltage sag and swell is big problem in power system. Sensitive load has a severe impact on itself due to voltage sag and swell. Dynamic Voltage Restorer (DVR) is a power customed device used in power distribution network. Matlab is an advanced simulation software used for effective modelling and simulation of DVR. Compensation for the control of voltage in DVR based on dq0 algorithm has been discussed here. To appropriately control the control targets for compensation voltage control, firstly the power circuit of a DVR systrm is analysed. The design is simple. The Simulation results are carried out by Matlab/Simulunk to verify the performance of the proposed method.